Clinical‐pathologic correlations in voltage‐gated Kv1 potassium channel complex‐subtyped autoimmune painful polyneuropathy. Issue 4 (13th February 2017) - Lahoria, Rajat; Pittock, Sean J.; Gadoth, Avi; Engelstad, Janean K.; Lennon, Vanda A.; Klein, Christopher J.
ABSTRACT: Introduction : Voltage‐gated Kv1 potassium channel complex (VGKC) autoantibodies subtyped for leucine‐rich glioma‐inactivated 1 (LGI1), contactin‐associated‐proteinlike 2 (CASPR2), and Kv IgGs have a spectrum of neurological presentations. Painful polyneuropathy is seen in some patients, but nerve pathology descriptions are lacking. Methods : Clinicopathologic features were studied in subtyped VGKC‐autoantibody‐seropositive patients who had undergone nerve biopsies. Results : Five patients were identified, 1 LGI1 IgG positive and 1 CASPR2 IgG positive, but all negative for Kv1.1‐, 1.2‐, 1.6‐subtyped IgG autoantibodies. Median symptom duration was 17 months. Pain was the predominant symptom; 3 had mild sensory loss and/or weakness. Histopathological abnormalities were limited to axonal loss in 3. None had mononuclear cellular infiltrates. Electron micrographs revealed no interstitial abnormalities. Three patients reported marked improvement in pain with immunotherapy. Conclusions : The nerve biopsy histopathology of patients subtyped for LGI1 and CASPR2 IgGs within the VGKC‐complex spectrum disorders shows either normal density or axonal fiber loss without inflammatory infiltrates. A reversible neural hyperexcitable mechanism is considered to be the cause of this painful polyneuropathy. Muscle Nerve 55 : 520–525, 2017